Expression of Value System in the Samogitian Daily Discourse of the 2nd Half of the 20th Century - Pajėdienė, Jūratė (Vilnius University Open Series, 2020)
The analysis of the material found in the sources of the Samogitian discourse of the second half of the 20th century, which builds upon the model of the categorization of values proposed by Viktor E. Frankl, makes it clear that the Samogitian daily discourse mainly focuses on creative values. Work is described as essential to everyone and making no harm to the human being. The person’s diligence is associated with one’s abilities, agility, understanding and trustworthiness, because many jobs require people’s collective action. Samogitians are convinced that diligence enables the person to live, to get rich and experience the meaning of life. Both personally and as a member of an ethnic community a Samogitian construes diligence as a quality giving an advantage over others and providing good grounds to brag. The possibility of subsistence and the quality of life are linked with work. However, excessive diligence is considered harmful, and therefore Samogitians advise not to forget common sense while working. The values which are based on experience and feeling are discussed far less commonly. In the sources of Samogitian discourse the expression of exper iential values is linked with joy and surprise about simple objects from the daily environment and the intention to draw the interlocutor’s attention towards them. Love is described as a universal feeling, but Samogitians are not prone to talk openly about it, unless they speak about the stories of their past. The person actualizes attitudinal values whenever he or she is confronted with the restrictions of life and reacts to the suffering sent by one’s fate. Samogitians are used to describe every person’s situation as resulting from the higher force or determined by one’s fate. The gift of life is described as meaningful per se and providing self-confidence. Hardships, troubles and pain are described as temporary conditions, which are easier to live through when one knows that it is always better to be alive than dead. Ethical values always require people to refuse certain temptations. Circumspection allows individuals to avoid deception in the form of abuse or flattery and to keep one’s dignity. The promotion of respect towards another and self-respect is based on the principle of equality by proposing not to treat others as you would not want them to treat you. The available sources of Samogitian discourse include a number of observations that the continuously improving conditions of life and work change people’s behaviour and values: an easier life changes people’s communication towards seclusion and alienation, reduces diligence and concern over the future, promotes effeminacy and lack of self-restraint expressed through the choice of a less virtuous lifestyle. According to interlocutors, the Samogitian language itself changes as well.